Facility and Service Analysis Kepatuhan Prinsip-Prinsip Syariah Hotel Asia Jaya Syariah Sarangan - Muhammad Harits; Ely Masykuroh (Institut Agama Islam Negeri Ponorogo, 2022)
Facility and service are essential parts that must exist in hotels, especially sharia hotels, which must pay close attention to facilities and services to support the hotel's success. This study aims to determine how facilities and services hotel constraints in carrying out compliance with sharia principles at Hotel Asia Jaya Syariah Sarangan. The results of this study are in terms of facilities at the Asia Jaya Syariah Hotel as a whole in accordance with Islamic law in the hospitality business, starting from the entertainment, consumption, ethical, and layout principles. Service, as a whole, has been good in implementing the six sharia principles. It's just that there are shortcomings in applying the consumption principle in restaurants because there is no supervision on how to slaughter the meat purchased. Constraints in sharia compliance from Hotel Asia Jaya Syariah Sarangan have not been able to comply with rules Numbers 3, 6, and 7 in the Fatwa of the National Sharia Council of the Indonesian Ulema Council No. 108/DSN-MUI/X/2016 concerning Guidelines for the Implementation of Sharia Tourism because they do not have a valid halal certificate. Issued by the Ministry of Religion, it does not yet have a hotel service procedure guide and has not used Islamic financial institutions' services.